Model of Interactive System for Training in the Proper Use of Hearing Protection Devices - GÓRSKI, Paweł (Archives of Acoustics, 2014)
In 2011, over 520 thousand persons worked in hazardous conditions (according to the GUS). Among hazardous factors related to working environment noise was found to be the most common one, threatening 199,6 thousand people (52.9% threats-per-persons related to working environment). The prevalence of workplace noise and increasing awareness of effects of its impact on the human body causes increase of the demand for knowledge of the methods of noise reduction. Due to the lack of knowledge concerning the proper use of hearing protectors, effective noise exposure in the real world may be about a dozen dB higher than the declared assumed protection value. For this reason, in Central Institute for Labour Protection – NRI “The interactive system for learning the correct use of hearing protectors” has been developed. The system includes a multimedia guide on hearing protectors supplemented by video tutorials, training materials with training hearing protectors, and software for evaluation of the activities of the trainee.